Spectrophotometric Study of Reaction Mechanism Between 2,3-Dichloro-5,6-dicyano-p-benzoquinone, 7,7,8,8- Tetracyanoquinodimethane π- and Iodine σ-Acceptors and Tiapride and Their Determination in Pure and Dosage Forms - H. SOLIMAN*, MADIHA; SAAD, H. (Asian Journal of Chemistry, 2024)
Three simple and accurate spectrophotometric methods are presented for the determination of antipsychotic drug, tiapride in pure and in different pharmaceutical preparations. The charge transfer (CT) reactions between tiapride as electron donor and 2,3-dichloro-5,6-dicyano-p-benzoquinone (DDQ),7,7,8,8-tetracyanoquinodimethane (TCNQ) as π-acceptors and iodine σ-acceptor reagents have been spectrophotometrically studied. The optimum experimental conditions have been studied carefully. Beer's law is obeyed over the concentration range of 15-120, 30-140 and 20- 120 μg mL-1 for tiapride using DDQ, TCNQ and iodine, respectively. Sandell sensitivity is found to be 0.050, 0.031 and 0.053 μg cm-2 for tiapiride using DDQ, TCNQ and iodine respectively, which indicate the high sensitivity of the proposed methods. The results are also confirmed by day precision of per cent recovery of 99.94-100.02, 99.91-100.4 and 99.90-100.11 % for DDQ, TCNQ and iodine methods, respectively. The data are comparable to those obtained by British and American Pharmacopeias assay for the determination of tiapride in raw materials and in pharmaceutical preparations.